Relationship between physical performance and quality of life in Charcot‐Marie‐Tooth disease: a pilot study. Issue 4 (7th December 2016) - Roberts‐Clarke, Daniel; Fornusek, Che; Saigal, Nidhi; Halaki, Mark; Burns, Joshua; Nicholson, Garth; Fiatarone Singh, Maria; Hackett, Daniel
Abstract: Charcot‐Marie‐Tooth (CMT) is a rare inherited peripheral neuropathy in which quality of life (QoL) is reduced compared with the general population. This paper investigates the relationship between QoL and physical performance in people with CMT with the aim of identifying avenues for future research into rehabilitation strategies. Cross‐sectional data was obtained from 10 participants (5 men, 5 women, age 46 ± 13 years, height 1.7 ± 0.1 m, body mass 77 ± 17 kg) with CMT (CMT1A n = 5; CMT‐X n = 3; unknown genetic origin n = 2). Participants were evaluated for QoL, falls efficacy (FES), balance, mobility, muscle strength, and power. Physical component score (PCS) of the Short Form‐36 (SF‐36) was significantly and directly related to higher leg press power (r = 0.75, p = 0.02). Better FES scores were significantly related to faster habitual gait speed (r = −0.70, p = 0.02), left hip abduction, and seated row strength (r = −0.68, p = 0.03; r = −0.73, p = 0.03, respectively). Future research should aim to substantiate these preliminary findings in a larger cohort and investigate whether interventions targeting muscle strength and power can improve QoL and mobility outcomes in people with CMT.